MESOPIC AND DARK-ADAPTED TWO-COLOR FUNDUS-CONTROLLED PERIMETRY IN GEOGRAPHIC ATROPHY SECONDARY TO AGE-RELATED MACULAR DEGENERATION. Issue 1 (January 2020) - Pfau, Maximilian; Müller, Philipp L.; von der Emde, Leon; Lindner, Moritz; Möller, Philipp T.; Fleckenstein, Monika; Holz, Frank G.; Schmitz-Valckenberg, Steffen
Abstract : Purpose: To investigate retinal sensitivity in the junctional zone of geographic atrophy (GA) secondary to age-related macular degeneration using patient-tailored perimetry grids for mesopic and dark-adapted two-color fundus-controlled perimetry. Methods: Twenty-five eyes with GA of 25 patients (prospective, natural-history Directional Spread in Geographic Atrophy study [DSGA; NCT02051998]) and 40 eyes of 40 normal subjects were included. Patient-tailored perimetry grids were generated using annotated fundus autofluorescence data. Customized software positioned test-points along iso-hulls surrounding the GA boundary at distances of 0.43°, 0.86°, 1.29°, 2.15°, and 3.01°. The grids were used for duplicate mesopic and dark-adapted two-color (cyan and red) fundus-controlled perimetry. Age-adjusted reference-data were obtained through regression analysis of normative data followed by spatial interpolation. Results: The mean sensitivity loss for mesopic testing decreased with the distance to GA (−10.3 dB [0.43°], −8.2 dB [0.86°], −7.1 dB [1.29°], −6.8 dB [2.15°], and −6.6 dB [3.01°]; P < 0.01). Dark-adapted cyan sensitivity loss exceeded dark-adapted red sensitivity loss for all iso-hulls (−14.8 vs. −11.7 dB, −13.5 vs. −10.1 dB, −12.8 vs. −9.1 dB, −11.6 vs. −8.2 dB, −10.7 vs. −8.0 dB; P < 0.01). Conclusion: Patient-tailored fundus-controlled perimetry grids allowed for testing of retinal function in the junctional zone of GA with high spatial resolution. A distinct decrease in mesopic sensitivity loss between 0.43° (125 µ m) and 1.29° (375 µ m) was observed that leveled off at more distant test-points. In proximity to the GA boundary, the results indicate that rod exceeded cone dysfunction. Abstract : Supplemental Digital Content is Available in the Text.Mesopic and dark-adapted two-color perimetry may now be performed with fundus tracking facilitating sensitivity testing in patients with instable fixation. Patient-tailored perimetry grids were developed to allow for refined testing of the junctional zone in geographic atrophy. The results indicate that in proximity to the geographic atrophy boundary, rod dysfunction exceeds cone dysfunction.